Economics and Knowledge - Hayek, Friedrich August von (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2015)
The author develops arguments to criticize the view that the equilibrium models mentioned by conventional economic theory are appropriate to reality. His argument shows the subjectivity inherent in the social science phenomena and shows the limitations of economic science, imposed both by the lack of complete knowledge and by its dispersion in society.